Evaluation of Sexual Assault Medical Forensic Exams: Payment Practices and Policies in the United States, 2011 - Zweig, Janine ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed. The qualitative Case Study data is not available as part of this data collection at this time.The purpose of the study was to examine: (1) which entities pay for sexual assault medical forensic exams (MFEs) in state and local jurisdictions throughout the United States, and the policies and practices around determining payment; (2) what services are provided in the exam process and how exams are linked to counseling, advocacy, and other services; (3) whether exams are provided to victims regardless of their reporting or intention to report the assault to the criminal justice system; (4) how MFE kits are being stored for victims who choose not to participate in the criminal justice system process; and (5) whether Violence Against Women Act (VAWA) 2005 requirements are generally being met throughout the country.Researchers conducted national surveys to obtain state-level information from state Services Training Officers Prosecutors (STOP) administrators (SSAs), victim compensation fund administrators, and state-level sexual assault coalitions. Surveys were distributed to potential respondents in all 50 states, the District of Columbia, and United States territories that held these state-level positions. Researchers also distributed local-level surveys though an extensive listserv maintained by the National Sexual Violence Resource Center (NSVRC). Researchers also conducted case studies in 19 local jurisdictions across six states were selected for case studies.Interviewees included the victim compensation fund administrator, state STOP administrator, state coalition director (or an appointed staff member) and sometimes crime lab or other state justice agency personnel, at the state level, and; law enforcement, prosecution, victim advocacy staff, and healthcare-based exam providers at the local level. Finally, researchers concluded each local jurisdiction visit with a focus group with victims of sexual assault. Data collection efforts included: a national survey of crime victim compensation fund administrators (Compensation Data, n = 26); a national survey of Services Training Officers Prosecutors (STOP) grant program administrators (SSA Data, n = 52); a national survey of state sexual assault coalitions (Coalitions Data, n = 47); and a survey of local community-based victim service providers (Local Provider Data, n = 489).